LEGAL PROTECTION OF THE RIGHTS OF WOMEN WORKERS - Susanti, Depi; Abas, Muhamad; Sadjat, Rizki (Awang Long Law Review, 2024)
Female workers are part of the workforce who carry out work, either for themselves or working in an employment relationship or under orders from employers or other legal entities. The reasons why women enter the world of work include the increasing need and the desire to qualify themselves with the abilities they have. The problem is how the legal protection for the rights of female workers is seen from Law Number 6 of 2023 concerning Job Creation and what are the obstacles in providing legal protection for female workers. Qualitative Research Method using the Normative Juridical approach method. The results of the research are that protection for women in the Job Creation Law is not specifically detailed, but in general the Job Creation Law mentions worker protection without discrimination as stated in Article 153 which was amended from Article 153 of the Manpower Law, in relation to protection of female workers at PT. Indo Marco Logistic includes 1) Protection of Female Workers regarding Menstrual Leave 2) Protection of the Right to Pregnancy and Childbirth Leave 3) Protection of the Right to Breastfeed 4) Protection of Female Workers Overtime and Barriers in Providing Legal Protection to Female Workers including 1) salary inequality between male and female workers who have the same responsibilities and qualifications. The work performed is similar, but the wages received by female workers are lower than their male counterparts. This is a violation of basic rights that must be corrected immediately. 2) Female workers often face discrimination during pregnancy. They are given the same workload without considering their physical and emotional condition. Maternity and paternity leave policies that should provide adequate rest are often ignored. 3) Companies employ female workers late at night without paying attention to health and safety risks. Female workers who are pregnant or have just given birth are prohibited from working from 23.00 to 07.00, but this rule is often ignored.